The Influence of Digital Literacy, Self-Efficacy and the Environment on Students Entrepreneural Intentions, Case Study of FEB Students at Muhammadiyah University of Jember Class of 2021-2024 - Pratama, Miko Rizky (Westscience Press, 2025)
The aim of this research is to examine the influence of digital literacy, self-efficacy and the environment on the entrepreneurial intentions of FEB Muhammadiyah University Jember students for the 2021-2024 academic year. This research uses associative quantitative methods, descriptive methodology, and multiple linear regression analysis on data from 93 respondents selected purposively. Research findings show that digital literacy, self-efficacy, and the surrounding environment have a positive and significant influence on students' entrepreneurial tendencies.